2015
DOI: 10.1182/blood-2014-09-551887
|View full text |Cite
|
Sign up to set email alerts
|

How I treat priapism

Abstract: Priapism is a disorder of persistent penile erection unrelated to sexual interest or desire. This pathologic condition, specifically the ischemic variant, is often associated with devastating complications, notably erectile dysfunction. Because priapism demonstrates high prevalence in patients with hematologic disorders, most commonly sickle cell disease (SCD), there is significant concern for its sequelae in this affected population. Thus, timely diagnosis and management are critical for the prevention or at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 113 publications
0
55
0
Order By: Relevance
“…Priapism, an unwanted erection lasting 4 h or more, occurs in 20% of men with HbSC and is a clinical emergency (Lionnet et al , ). Priapism often occurs as young men reach sexual maturity (Adeyoju et al , ), and may be the presenting sign of HbSC disease in previously undiagnosed men (Anele et al , ). Typically caused by acute ischaemic injury, priapism may be continuous, intermittent or recurrent (stuttering priapism).…”
Section: Systemic Complicationsmentioning
confidence: 99%
“…Priapism, an unwanted erection lasting 4 h or more, occurs in 20% of men with HbSC and is a clinical emergency (Lionnet et al , ). Priapism often occurs as young men reach sexual maturity (Adeyoju et al , ), and may be the presenting sign of HbSC disease in previously undiagnosed men (Anele et al , ). Typically caused by acute ischaemic injury, priapism may be continuous, intermittent or recurrent (stuttering priapism).…”
Section: Systemic Complicationsmentioning
confidence: 99%
“…Studies that focus on the development of new preventive therapies are of great clinical relevance. Alterations of the nitric oxide (NO)-cGMP-phosphodiesterase-5 (PDE5) signaling pathway have been implicated as a major mechanism for priapism in SCD, which is not simply a consequence of vascular blockage (Kato, 2012;Anele et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this condition, the mechanisms of erection are entirely normal, but there appears to be a lack of mechanisms which control the returning of the penis to its flaccid state. Therefore, prolonged uncontrolled erections are seen in priapism [ 21 ]. Histopathologic studies have shown that tissue damage is dependent on the duration of the erection and irreversible damage occurs after 6 h. [ 22 ].…”
Section: Discussionmentioning
confidence: 99%